Trophic State Waters of Kolong Tin Post Mining inBaranTimurVillage Meral District KarimunRegency Kepulauan Riau Province Based on Nitrate and Phosphate - Sihombing, Evi Stevani; Dahril, Tengku; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThere were many activites that take place in kolong of tin post mining in BaranTimurVillage MeralDistrictKarimunRegency Kepulauan Riau Province,One of which is fishery activites suspected to provide input in the form of leftover food and metabolic that influenced concentration of nutrient(N and P) in the water.This research aims to know the trophic state in ex-tin mining the ponds kolong of tin post mining in BaranTimur Village Meral District KarimunRegency Kepulauan Riau Provincebased on nitrate and phosphate concentration.A research was conducted during July 2019. There were three stations namely station 1 (inlet area), station 2(in middle of kolong) and station 3 (outlet area). There were 3 vertical sampling points, in the surface, in 2 Secchidepthand in 4 Secchi depth. Sampling was done 3 times, once/week. Water quality parameters measured were nitrate, phosphate, temperature, transparency, pH, dissolved oxgen, and carbon dioxide. Results shown that the nitrate 0.043-0.061 mg/L, phosphate 0.085-0.125 mg/L, temperature 30.3-310C, transparency73.3-78 cm, depth 4-7 m, pH 5, dissolved oxygen 4.10-6.91 mg/L and carbon dioxide 3.32-7.32 mg/L. Based on nitrate concentration,the trophic state in ex-tin mining the ponds of Kolong Tin Post Mining in Baran Timur Village Meral District KarimunRegency Kepulauan Riau Province was oligotrophic, while based on phosphate concentration, it can be categorized as mesotrophic.Â Keyword :trophic state, nitrate, phosphateÂ